THE DEGRADATION AND FRAGILITY OF SOILS IN SOUTHWESTERN GOIAS: THE WATERSHED CASE OF RIBEIRAO DA PICADA - Estevam-Alves, Régia (2016)
This paper presents a reflection on the degradation of soils from the environmental fragility point of view, having as area of study the watershed of Ribeirao da Picada/GO. For this purpose, the potential and emerging fragility of that watershed has been established by using information and data on climate, soils, slope, rainfall erosivity and land use. In addition, there was a literature review on the issue of land degradation and methodologies used to establish the environmental fragility. The results showed us that the preparation of the environmental fragility makes it possible to know the characteristics of the watershed environment, allowing the identification of areas that are more prone to degradation.